The Trump Doctrine and the Emerging International System
XXXIII, 398 p. 12 illus., 10 illus. in color.
Keywords: President Donald J. Trump’s “America First” outlook has inspired both enthusiasm and condemnation among different segments of the American population. This book examines the meaning and implications of that perspective, and how the Trump Administration has implemented it—or failed to do so. Contributors, subject-matter experts with diverse points of view, place the Trump Doctrine within the succession of presidential foreign policy themes, and provide a case-by-case analysis of how it has been applied in specific regions and countries around the world. The book’s aim is to provide a fair and balanced assessment, relatively rare in this period of intense partisanship and impending national election. Stanley Renshon is Professor of Political Science at the City University of New York, Herbert H. Lehman College and the Graduate School and University Center, USA, and a certified psychoanalyst. Peter Suedfeld is Dean Emeritus of Graduate Studies and Professor Emeritus of Psychology at the University of British Columbia, Canada.